2021
DOI: 10.1126/sciadv.abf2856
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H 1 and H 2 receptors are essential transducers of the integrative exercise training response in humans

Abstract: Exercise training is a powerful strategy to prevent and combat cardiovascular and metabolic diseases, although the integrative nature of the training-induced adaptations is not completely understood. We show that chronic blockade of histamine H1/H2 receptors led to marked impairments of microvascular and mitochondrial adaptations to interval training in humans. Consequently, functional adaptations in exercise capacity, whole-body glycemic control, and vascular function were blunted. Furthermore, the sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…Importantly, they also found that several histamine receptormediated adaptations were interrelated, as increases in VO 2max were related to changes in vascular function and whole-body insulin sensitivity. Moreover, a correlation was found between changes in capillary-fiber ratio and whole-body insulin sensitivity (Van der Stede et al, 2021). These findings are consistent with recent research suggesting that the post-exercise activation of H 1 -and H 2 -receptors upregulate several related pathways, including those related to metabolism, endothelial and vascular function (Romero et al, 2016), thereby highlighting important histaminergic adaptations to exercise that potentially impact both post-exercise blood flow and metabolic regulation.…”
Section: Discussion: Future Directionssupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, they also found that several histamine receptormediated adaptations were interrelated, as increases in VO 2max were related to changes in vascular function and whole-body insulin sensitivity. Moreover, a correlation was found between changes in capillary-fiber ratio and whole-body insulin sensitivity (Van der Stede et al, 2021). These findings are consistent with recent research suggesting that the post-exercise activation of H 1 -and H 2 -receptors upregulate several related pathways, including those related to metabolism, endothelial and vascular function (Romero et al, 2016), thereby highlighting important histaminergic adaptations to exercise that potentially impact both post-exercise blood flow and metabolic regulation.…”
Section: Discussion: Future Directionssupporting
confidence: 90%
“…In addition to investigations examining the acute effects of post-exercise vasodilation on glucose regulation, future investigations are needed to examine emerging interactions between vascular and metabolic adaptions to exercise. Along those lines, Van der Stede et al (2021) observed that histamine receptor blockade blunted post-exercise muscle perfusion and increases in whole body insulin sensitivity in response to 6 weeks of high-intensity interval training in healthy males. Importantly, they also found that several histamine receptormediated adaptations were interrelated, as increases in VO 2max were related to changes in vascular function and whole-body insulin sensitivity.…”
Section: Discussion: Future Directionsmentioning
confidence: 90%
“…For instance, the exercise-induced increase in glucose uptake is dependent on an increase in blood perfusion ( McConell et al., 2020 ). Moreover, inhibition of vasodilation and angiogenesis in response to exercise impaired exercise-induced increases in performance ( Van der Stede et al., 2021 ). We did not observe a difference in performance, muscle oxidative parameters, or fiber-type changes.…”
Section: Discussionmentioning
confidence: 99%
“…The sample volume was maximized to the artery diameter with care taken to avoid interference of the vessel walls and a standard low-velocity rejection filter was applied. Femoral artery diameter was determined in triplicate during systole with the built-in calipers [ 23 ].…”
Section: Methodsmentioning
confidence: 99%